Interface Hepatitis over Grade 2 May Differentiate Chronic Inflammation Associated with CHB from NAFLD in the Early Stage - Yong-fen Zhu; Jin Wang; Jia-zhui Fang; Qiao Yang; Fang-fang Lv (Gastroenterology Research and Practice)
Background. Patients with chronic hepatitis B (CHB) concomitant with nonalcoholic fatty liver disease (NAFLD) are increasing. Objectives. To identify pathological features that can be used to differentiate between chronic inflammation caused by CHB and that caused by NAFLD. Methods. Patients with CHB (n=31) needing antiviral treatment, NAFLD (n=50), or CHB-NAFLD (n=51) who underwent biopsy were retrospectively enrolled. Pathological characteristics of chronic inflammation were evaluated using the METAVIR scoring system. The rates of three pathological characteristics were first compared in patients with NAFLD and those with CHB, then compared after fibrosis matching, and were finally compared in CHB-NAFLD patients with different viral loads. Results. The rates of interface hepatitis over grade 2 and fibrosis over grade 2 were significantly higher in the CHB group than in the NAFLD group (100% vs. 4% and 80.6% vs. 22%; both P<0.0001), while no significant difference was observed in the rate of lobular inflammation over grade 2 between the two groups. After fibrosis matching, in patients with F0–2 fibrosis, the rate of interface hepatitis over grade 2 in CHB was significantly higher than that in NAFLD (100% vs. 0%; P<0.0001). In CHB-NAFLD patients with F0–2 fibrosis, the rate of interface hepatitis over grade 2 in cases with a high viral load was significantly higher than cases with a low viral load (66.6% vs. 0%; P<0.0001). The rate of lobular inflammation showed no difference between groups. Conclusion. Interface hepatitis over grade 2 can be used for the differential diagnosis of chronic inflammation associated with CHB or NAFLD in the early stage.